EARLY DETECTION OF HEARING IMPAIRMENTS TRAINING: ENHACING COMMUNITY HEARING HEALTH DEGREES IN PACITAN, EAST JAVA - Puguh Setyo Nugroho; Rosa Falerina; Rizka Fathoni Perdana; Zakiyatul Faizah; Azhar Nur Fathoni; Agde Muzaky Kurniawan; Danial Habri Arsy (Jurnal Layanan Masyarakat (Journal of Public Services), 2023)
Humans are social beings who always communicate with other individuals. The ear as a hearing organ has a big role in the communication process. Disorders of the ear will cause disturbances in individual communication and socialization with other individuals in society. Efforts to maintain and improve hearing health are the responsibility of all parties, especially doctors in primary health services as the spearhead of efforts to detect early public health, so that the quality of these doctors must be maintained. Pacitan, one of the districts in the province of East Java, has a mountainous area, that accessibility is quite difficult and remote. The availability of human resources and health infrastructure in Pacitan, which is quite limited, requires the ability to carry out early detection and management of hearing loss in the community. Therefore, community service activities were carried out in the form of training on early detection and management of hearing impairments for doctors throughout Pacitan district. The activity was attended by 47 general practitioners who were delegates from health facilities. The pre test results obtained an average value of 45.23 and the post test was 68.55. There is an increase in knowledge before and after the activity.